Perancangan Aplikasi Kesehatan Mental berbasis Mobile Menggunakan Metode Design Thinking - Theophillia, Geona; Chandra, Cyntia (Fakultas Komputer - Universitas Universal, 2023)
The purpose of this research is to determine an application prototype to giving more Annoymous Feature so that they can easily speak up what problem that they embarrassed or feel ashamed to talk to. The problem that we’re having at the moments is that user can’t be freely to speak up because of scared that people look at them as an person that want attention from others also a weak person that can’t handle something like that which its make people have some mental disorder that will risk to death if not assisted immediately. Design Thinking have five stages are involved which is emphatizing, defining, ideation, prototype and testing. The goal of this study is for made an innovation about mental health application and hope that they can interact to communicate without feel being judge.